EFL TEACHERS’ PERCEPTION ON THE USE OF ROLE PLAY IN SPEAKING CLASS - Yenni Widiarti Widiarti; Irma Windy Astuti (STBA Pontianak, 2023)
This research aims to describe two English teachers’ perceptions regarding their experience in using role play to facilitate the students’ speaking practice at different English courses in Yogyakarta. The research participants are two teachers teaching speaking skills and have used role-play as one of the tasks in their classes. The researchers employed a descriptive qualitative design and thematic analysis to collect and examine the data obtained from interviews. The findings show that the use of role-play was: driven by the classes’ learning objectives, necessarily taking real life-like situation set up, having generally a significant impact on the students’ speaking fluency whilst boosting their confidence and on occasion, gaining various responses from the students.